2018
DOI: 10.1038/s41467-018-07077-1
|View full text |Cite
|
Sign up to set email alerts
|

H3K9 methyltransferases and demethylases control lung tumor-propagating cells and lung cancer progression

Abstract: Epigenetic regulators are attractive anticancer targets, but the promise of therapeutic strategies inhibiting some of these factors has not been proven in vivo or taken into account tumor cell heterogeneity. Here we show that the histone methyltransferase G9a, reported to be a therapeutic target in many cancers, is a suppressor of aggressive lung tumor-propagating cells (TPCs). Inhibition of G9a drives lung adenocarcinoma cells towards the TPC phenotype by de-repressing genes which regulate the extracellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 52 publications
(77 reference statements)
2
48
0
Order By: Relevance
“…Our work and that of others (Avgustinova et al 2018;Rowbotham et al 2018) warn that the treatment of cancers with inhibitors of H3K9-HMTs may augment genomic instability and thus, in the long run, favor more severe forms of cancer. On the other hand, for tumors that are deficient for BRCA1, treatment with G9a or other H3K9-HMT inhibitors may enhance cell death, like the synthetic lethality we score in worms.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Our work and that of others (Avgustinova et al 2018;Rowbotham et al 2018) warn that the treatment of cancers with inhibitors of H3K9-HMTs may augment genomic instability and thus, in the long run, favor more severe forms of cancer. On the other hand, for tumors that are deficient for BRCA1, treatment with G9a or other H3K9-HMT inhibitors may enhance cell death, like the synthetic lethality we score in worms.…”
Section: Discussionmentioning
confidence: 55%
“…The more than additive appearance of satellite transcripts and R loops in met-2 and brc-1 mutants, but not in the set-25 mutant, argues that the expression of simple repeats, and not transposons, renders cells highly dependent on the BRCA1/BARD1 complex. Since different HMTs target the classes of repeats independently, this has important implications for the treatment of tumors with H3K9-HMT inhibitors (Rowbotham et al 2018). Two recent studies have highlighted the fact that inhibitors of G9a, one of the HMTs responsible for H3K9me2 levels in mammalian cells, leads to genome instability and the delayed appearance of highly aggressive forms of skin and lung tumors (Avgustinova et al 2018;Rowbotham et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent studies have suggested that 449 the effects of epigenetic inhibitors can be more complex, and are likely to be context-dependent. For instance, 450 two recent studies have shown that inhibition of G9a drives the formation of tumors with more aggressive, 451 stem-like phenotypes Rowbotham et al, 2018). In the study by Avgustinova et al,452 G9a knock out delayed the formation of carcinogen-induced skin tumors, but once G9a-knockout tumors 453 formed they were more aggressive, with higher levels of genomic instability and more frequent p53 loss 454 .…”
Section: Discussion 385mentioning
confidence: 99%
“…For example, some studies revealed a global loss of acetylated H4-lysine 16 (H4K16ac) and H4-lysine 20 trimethylation (H4K20me3) in different cancer cell lines and primary tumors, such as leukemia, breast, lung, and colon cancer (89). In addition, alterations of H3K9me and H3K27me patterns are also observed in different types of human cancer, including bladder, colorectal, glioma, breast, and lung cancer (90)(91)(92)(93)(94). Accordingly, the expression of enzymes responsible for these modifications, histone acetylases/ deacetylases (HATs and HDACs) and histone methyltransferases (HMTs), is observed to be dysregulated in cancer.…”
Section: Histone Modifications and Canine Cancermentioning
confidence: 99%